Pancasila Sebagai Integritas Ideologi Negara Yang Berkedaulatan - Rahma Yulia Sifa; Ridwan, Muannif (AL-BAHTS: Jurnal Ilmu Sosial,Politik, dah Hukum, 2025)
Pancasila consists of two words, namely, "Panca" which means five and, "Sila", which means a principle or principle. From these two words, Pancasila can be interpreted as the five principles, which of course act as the fundamental foundation of the Unitary State of the Republic of Indonesia (NKRI). Remaining the basis of the state, Pancasila is of course the foundation of all values, ethics and standards that support life in the eyes of society, nation and state. Pancasila will absolutely regulate and become the direction of the nation's personality, national characteristics and the ideals of this sovereign state. In carrying out its role, Pancasila will contribute to the formation of the character and morals of every individual who is an Indonesian citizen. For this reason, Pancasila has an important role as a belief system or foundation of the state, as well as a philosophy of honor for a sovereign state, namely the Unitary State of the Republic of Indonesia. This research will discuss the functions, roles and challenges in maintaining Pancasila as the basis of state thought and ideology as well as maintaining the trustworthiness of state ideology within the framework of a sovereign state.